2019
DOI: 10.3332/ecancer.2019.915
|View full text |Cite
|
Sign up to set email alerts
|

Perception of tobacco use in young adults in urban India: a qualitative exploration with relevant health policy analysis

Abstract: Tobacco is one of the biggest global health concerns of this century with a significant contribution to the increasing burden of cancers, chronic diseases and associated mortality. Tobacco-related cancers are one of the commonest causes of cancer-related mortality in low- and middle-income countries (LMICs). The tobacco epidemic is constantly on the rise, affecting LMICs in particular due to a lack of awareness in the population, insufficient health infrastructure and weak regulatory interventions. India is ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…This is further compounded by poor access to drug deaddiction-centres and a lack of stringent implementation of tobacco control measures in rural areas. 5 To overcome the rural–urban disparities and give an impetus to the awareness campaign in rural areas, the Panchayati Raj institutions can provide a platform for awareness campaigns with active participation by local bodies like the Sarpanch and village elderly. Furthermore, the primary healthcare centres can function as the first point of contact for advice and treatment of tobacco addiction by providing specific pharmacotherapeutic and psychosocial interventions to help quit for those seeking help.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is further compounded by poor access to drug deaddiction-centres and a lack of stringent implementation of tobacco control measures in rural areas. 5 To overcome the rural–urban disparities and give an impetus to the awareness campaign in rural areas, the Panchayati Raj institutions can provide a platform for awareness campaigns with active participation by local bodies like the Sarpanch and village elderly. Furthermore, the primary healthcare centres can function as the first point of contact for advice and treatment of tobacco addiction by providing specific pharmacotherapeutic and psychosocial interventions to help quit for those seeking help.…”
Section: Discussionmentioning
confidence: 99%
“… 3 4 The tobacco epidemic is steadily on the rise, affecting LMICs due to a lack of awareness in the population, insufficient health infrastructure and weak regulatory interventions. 5 India is home to 275 million tobacco users and is second only to China in tobacco products. 6 In India, tobacco is responsible for one-tenth (1 million) of all the deaths each year and a significant burden of cancer cases (45% of male’s cancer and 20% of female’s cancer).…”
Section: Introductionmentioning
confidence: 99%
“…Pattanayak et al, (2012) studied the perceived health risk, and readiness to quit and reported inadequate knowledge, low-risk perception, casual attitude for tobacco-related health risks, and higher perceived ability to quit tobacco was seen among the bipolar disorder patients. Lack of available support for tobacco cessation, leading to failure in quitting, a lack of understanding about the ill effects of tobacco and an overall lack of belief in the existing tobacco control measures were some of the perceptions of tobacco use among the youth of India (Ghose et al, 2019). Delbarre and Aghi (2013) conducted a qualitative study among the vulnerable population of India and France and reported that the study participants anticipated quitting to be extremely challenging, and especially the Indian participants had negative perception towards quitting and believed smokeless tobacco actually improved their health.…”
Section: Evaluation Of Perceptions Of Tobacco Cessation Among the Individuals Attending A Tertiary Care Dental Hospital -A Mixed Methods mentioning
confidence: 99%
“…The number of published policy analysis addressing tobacco control in India is scarce even though there are a significant amount of analyses done in other LMICs such as China [ 17 ] and Brazil [ 18 ], making the need for a policy analysis stronger. We have published previously on the strengths and gaps in the national tobacco policy and contrasted this with the qualitative data obtained from young adult tobacco users [ 19 ]. The goal of the present paper is twofold: a) analyse India’s tobacco control policies considering the WHO-FCTC, identify barriers and gaps, b) reflect on key stakeholders’ perspectives and recommend opportunities for policy reforms.…”
Section: Introductionmentioning
confidence: 99%